Answer:
6
Explanation:
Simplify the following:
sqrt(64) + sqrt(225) - sqrt(64 + 225)
Hint: | Evaluate 64 + 225.
64 + 225 = 289:
sqrt(64) + sqrt(225) - sqrt(289)
Hint: | Simplify radicals.
sqrt(289) = sqrt(17^2) = 17:
sqrt(64) + sqrt(225) - 17
Hint: | Simplify radicals.
sqrt(64) = sqrt(2^6) = 2^3:
2^3 + sqrt(225) - 17
Hint: | In order to evaluate 2^3 express 2^3 as 2×2^2.
2^3 = 2×2^2:
2×2^2 + sqrt(225) - 17
Hint: | Evaluate 2^2.
2^2 = 4:
2×4 + sqrt(225) - 17
Hint: | Multiply 2 and 4 together.
2×4 = 8:
8 + sqrt(225) - 17
Hint: | Simplify radicals.
sqrt(225) = sqrt(15^2) = 15:
8 + 15 - 17
Hint: | Evaluate 8 + 15 - 17.
8 + 15 - 17 = 6:
Answer: 6